Uso do tanino vegetal como agente floculante de microalgas: estudo de caso de tratamento de efluente de cervejaria - Tonhato Junior, Alcides (2015)
The brewing industry is a very important sector in the world’s economy, and its production process generates a large amount of wastewater, around 4-11 liters of effluent per liter of beverage produced. It is essential the proper treatment of this wastewater and microalgae are being considered a promising way of effecting treatment and, in addition, generate biomass rich in compounds of interest. A significant amount of biomass from the wastewater is recovered by the process of coagulation/flocculation/sedimentation. When using vegetable tannin as an organic flocculant, biomass can be directed to the preparation of organic fertilizer, unlike what would occur if using a flocculant from some other metal base, since some are considered toxic. This work presents a study on the use of vegetable tannin as an organic flocculant (Tanfloc SL®) in the treatment of brewery wastewater. Initially it was tested the coagulation/flocculation/sedimentation of crude brewery wastewater without any pretreatment and without microalgae. Subsequently it was tested the separation of microorganisms that are generated in industrial treatment, such as microalgae and other organisms in suspension. Assays were performed using Jar Test. The data show that the best floculation results in crude brewery wastewater was in the conditions: Tanfloc SL® (0.28 mL.L-1) at pH 5.3, resulting in 95.52% removal of turbidity and 93.30% removal of apparent color, as for the flocculation of microorganisms in suspension was used 0.12 mL.L-1 at pH 4.5, resulting in 98.58% and 99.14% respectively. Also, after the process of coagulation/flocculation/sedimentation of microorganisms in suspension it was analyzed the removal percentage of some contaminants such as ammonia (64.1% removal), nitrite (80.0% removal), nitrate (88.0%), total phosphorus (70.6%), COD (85.7%), BOD (22.9%) and total solids (31.7%).